P052 Auto-antibodies against post translational modified proteins in osteoarthritis: pilot data comparing synovial fluid and sera. (March 2019) - Xie, X; Delft, MV; Trouw, L; Conaghan, P; Ponchel, F
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Osteoarthritis (OA) is a highly prevalent disease and a leading cause of disability worldwide. OA is age-related and as such has a potential devastating impact on our ageing populations. The pathogenesis of OA remains poorly understood. Inflammatory responses are prevalent in driving processes associated with aging, and increased levels of IgG autoantibodies (auto-Abs) have been associated with age. In OA, auto-Abs are also frequently observed, notably towards post translational modified (PTM) proteins. Such PTM are often the result of inflammation-driven mechanisms such as oxidative stress, carbamylation and citrullination 1 in OA joints. Objectives: To establish a profile of auto-Abs associated with PTM in OA and controls. Methods: Serum was collected from healthy controls (HC) and OA patients as well as rheumatoid arthritis (RA); knee synovial fluid (SF) samples were collected from OA/RA patients. All participants gave informed consent. The levels of antibodies against citrullinated protein antigens (ACPA) was measured (Phadia CCP-test), antibodies against carbamylated proteins (anti-CarP) were measure in collaboration with Leiden using an in-house ELISA, 2 antibodies against glycated-collagen proteins (anti-ROS-CII) were analysed using an in house ELISA. 3 Results: ACPA positivity was present in 6% (n=24/392) of OA patients' serum, which was 3 times more frequent that in HC (∼2%), but was present in 48% (n=22/46) of OA SF. RA frequencies were 73% (n=41/56) in SF and 65% (n=55/85) in serum. Anti-CarP auto-antibodies were detected in 11% (n=12/111) of OA sera and in 37% (n=127/340) of RA sera (SF results are not yet available). Anti-collagen auto-Abs in serum were observed at similar frequencies: 18% of OA (n=6/34) and 18% (n=14/78) of RA patients, but only 6.7% (n=3/45) of OA fluids and 3.6% (n=2/56) of RA fluids were positive. Collagen modified by reactive oxygen species enables detection of auto-Ab (anti-ROS-CII); these were observed in 35% (n=12/34) of OA and 32% (n=25/78) of RA sera; this differed from SF with 20% positive (n=9/45) in OA and 60% (n=34/56) in RA. Conclusions: In OA patients, autoimmune responses against native proteins (especially collagens and proteoglycans) have been reported since the 1980's, notably in relation with severity. 4 However, our data demonstrate that auto-Abs may also result from the accumulation of PTMs induced by chemical reactions in the inflamed joint. These auto-Abs against PTM-antigens may also be contributing to disease severity, as these are notably frequently detected in SF even if a bit less frequently than in RA in our pilot cohorts. References: Burska AN. MI 2014;492873–492873. Shi J, et al. ART 2015;17:339. Strollo R, et al. A&R 2013;65:1702–12. Yuan GH, et al. A&R 2003;48:602–611. Disclosure of Interest: None declared